High-Dose Cytomegalovirus (CMV) Hyperimmune Globulin and Maternal CMV DNAemia Independently Predict Infant Outcome in Pregnant Women With a Primary CMV Infection. (20th October 2019) - Nigro, Giovanni; Adler, Stuart P; ,
Abstract: Background: After primary maternal cytomegalovirus (CMV) infection during pregnancy, infants are at risk for disease. Methods: Factors predictive of infant outcome were analyzed in a database of 304 pregnant women with primary infection. These women were enrolled between 2010 and 2017 and delivered 281 infants, of whom 108 were CMV infected. Long term follow-up occurred for 173 uninfected and 106 infected infants at age 4 years (range, 1–8 years). One hundred fifty-seven women were treated with an average of 2 doses (range, 1–6 doses) of high-dose hyperimmune globulin (HIG: 200 mg/kg/infusion). We used a regression model to define predictors of fetal infection, symptoms at birth, and long-term sequelae; 31 covariates were tested. Results: Four factors predicted fetal infection: a 1.8-fold increase (30% vs 56%) in the rate of congenital infection without HIG (adjusted odds ratio [AOR], 5.2; P < .0001), a 1.8-fold increase (32% vs 56%) associated with maternal viral DNAemia prior to HIG administration (AOR, 3.0; P = .002), abnormal ultrasounds (AOR, 59; P = .0002), and diagnosis of maternal infection by seroconversion rather than avidity (AOR, 3.3; P = .007). Lack of HIG and abnormal ultrasounds also predicted symptoms ( P = .001). Long-term sequelae were predicted by not receiving HIG (AOR, 13.2; P = .001), maternal infection in early gestation (odds ratio [OR], 0.9; P = .017), and abnormal ultrasounds (OR, 7.6; P < .003). Prevalence and copy/number of DNAemia declined after HIG. Conclusions: Maternal viremia predicts fetal infection and neonatal outcome. This may help patient counseling. High-dose HIG may prevent fetal infection and disease and is associated with the resolution of DNAemia. Abstract : Among 304 women with a primary cytomegalovirus infection during pregnancy four factors independently predicted fetal infection: not receiving high-dose immunoglobulin (HIG); maternal viral DNAemia before HIG administration; an abnormal ultrasound; and diagnosis of maternal infection via seroconversion rather than avidity.